Understanding the scientific validity of synthetic torpor for radiation research and extended space missions - Kokko, Anggraeini Puspitasari; Chowdhury, Reema; Sherman, Katelin; Cerri, Matteo; Tinganelli, Walter (Frontiers in Space Technologies, 2024)
The idea of synthetic torpor, an artificial state resembling the hypo-metabolic state of torpor/hibernation, has recently gained significant scientific attention. Building on pioneering research demonstrating the protective effects of torpor against radiation in mammals, this mini-review aims to evaluate its scientific validity. We will explore the theoretical foundations, practical applications, and potential challenges linked to synthetic torpor. By critically examining the current knowledge, we aim to determine if synthetic torpor is a scientifically viable and achievable concept with broad implications for fields such as space exploration and healthcare.